2018
DOI: 10.1152/jn.00702.2017
|View full text |Cite
|
Sign up to set email alerts
|

Organ of Corti vibration within the intact gerbil cochlea measured by volumetric optical coherence tomography and vibrometry

Abstract: There is indirect evidence that the mammalian cochlea in the low-frequency apical and the more commonly studied high-frequency basal regions function in fundamentally different ways. Here, we directly tested this hypothesis by measuring sound-induced vibrations of the organ of Corti (OoC) at three turns of the gerbil cochlea using volumetric optical coherence tomography vibrometry (VOCTV), an approach that permits noninvasive imaging through the bone. In the apical turn, there was little frequency selectivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 74 publications
(109 reference statements)
0
33
0
Order By: Relevance
“…The longitudinally carried TM radial motion may be more important than TM resonances, but in vivo TM motion is poorly understood and is likely different from the classic view. In addition, recent experiments show that the reticular lamina moves much more than the BM, and there is differential motion between structures at the top of the OoC, such as rotation of the reticular lamina (2)(3)(4)(5)(6)(7)(8)46). All of the above indicate that the classic view in Fig.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The longitudinally carried TM radial motion may be more important than TM resonances, but in vivo TM motion is poorly understood and is likely different from the classic view. In addition, recent experiments show that the reticular lamina moves much more than the BM, and there is differential motion between structures at the top of the OoC, such as rotation of the reticular lamina (2)(3)(4)(5)(6)(7)(8)46). All of the above indicate that the classic view in Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Considering these observations, the overall pattern of OSL and bridge motion we have seen in the base is likely present throughout the human cochlea. This does not rule out there being differences in cochlear motions between base and apex as has been found in laboratory animals (5,6,8).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Third, it is well documented that only sensitive living cochleae can amplify sounds [19][20][21][22][23] and generate distortion product otoacoustic emissions [24][25][26] . The basilar membrane distortion 8,9,27,28 and the reticular lamina nonlinearity [29][30][31][32][33][34][35][36] vanish upon the death of the animals before the outer hair cells can be isolated. Thus, whether the outer hair cells can generate distortion products at high frequencies in living cochleae remains unknown.…”
mentioning
confidence: 99%
“…Fourth, it is well known that harmonic components of perceived pitch transition from resolved to unresolved around 1–2 kHz ( Plack et al, 2006) . Lastly, advances in cochlear imaging show that the micromechanical vibrations of the cochlea are different between base and apex [e.g., Dong et al (2018) ], with large differences in tuning sharpness. While recent modeling efforts have made progress in reconciling these differences in apical and basal sound processing for mammals ( Sasmal and Grosh, 2019) , it has been suggested that the human cochlea may be different in many regards from the canonical viewpoint of a relatively generic cochlear structure/physiology/function across mammals ( Joris et al, 2011 ; Raufer et al, 2019) .…”
Section: Discussionmentioning
confidence: 99%